On the kernel estimation of a multivariate distribution function under positive dependence - Azevedo, Cecília Maria (2011)
In this paper, we consider the kernel estimator of the p-dimensional marginal distribution function of a stationary, positively associated sequence of random variables. For this setting, we state results concerning the asymptotic behaviour of this estimator extending some characterizations available in the literature. In addition, we present a simulation study about the empirical process constructed from such a estimator illustrating its asymptotic normality.